Chondroitin sulfate-hybridized zein nanoparticles for tumor-targeted delivery of docetaxel. (1st February 2021) - Lee, Han Sol; Kang, Nae-Won; Kim, Hyelim; Kim, Dong Hyun; Chae, Jung-woo; Lee, Wonhwa; Song, Gyu Yong; Cho, Cheong-Weon; Kim, Dae-Duk; Lee, Jae-Young
Highlights: Zein/CS NPs possess enough colloidal stability for intravenous administration. Zein/CS NPs exhibit enhanced tumor targetability via interaction with CD44. Zein/CS NPs display improved anti-tumor efficacy with negligible systemic toxicity. Abstract: Chondroitin sulfate-hybridized zein nanoparticles (zein/CS NPs) were developed for targeted delivery of docetaxel, which exhibited mean diameters of 157.8 ± 3.6 nm and docetaxel encapsulation efficiency of 64.2 ± 1.9 %. Docetaxel was released from the NPs in a sustained manner (∼72 h), following first-order kinetics. The zein/CS NPs showed improved colloidal stability, maintaining the initial size in serum for 12 h. The pre-treatment of CS reduced the uptake efficiency of the NPs by 23 % in PC-3 cells, suggesting the involvement of CD44-mediated uptake mechanism. The NPs showed 2.79-fold lower IC50 values than free docetaxel. Enhanced tumor accumulation of the NPs was confirmed in PC-3 xenograft mice by near-infrared fluorescence imaging (35.3-fold, versus free Cy5.5). The NPs exhibited improved pharmacokinetic properties (9.5-fold longer terminal half-life, versus free docetaxel) and anti-tumor efficacy comparable to Taxotere with negligible systemic toxicity, suggesting zein/CS NPs could be a promising nanoplatform for targeted cancer therapy.